2016
DOI: 10.1001/jamaophthalmol.2016.3277
|View full text |Cite
|
Sign up to set email alerts
|

Use of Alleviating Maneuvers for Periocular Facial Dystonias

Abstract: IMPORTANCE Patients with benign essential blepharospasm or hemifacial spasm are known to use botulinum toxin injections and alleviating maneuvers to help control their symptoms. The clinical correlates between the use of botulinum toxin injections and the use of alleviating maneuvers are not well established. OBJECTIVE To determine whether the use of alleviating maneuvers for benign essential blepharospasm or hemifacial spasm correlates with disease severity or botulinum toxin treatment. DESIGN, SETTING, AND P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Additionally, the patient has added security in their everyday life, as the possibility of personal injury is reduced, in turn reducing the burden on family members [52]. A case controlled study found no link between the combined use of alleviating maneuvres (touching specific areas of the face, i.e the upper eyelid) and BTX treatment with better QoL outcomes [60].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the patient has added security in their everyday life, as the possibility of personal injury is reduced, in turn reducing the burden on family members [52]. A case controlled study found no link between the combined use of alleviating maneuvres (touching specific areas of the face, i.e the upper eyelid) and BTX treatment with better QoL outcomes [60].…”
Section: Resultsmentioning
confidence: 99%
“…Sensory inputs, including pain, touch, and proprioception, are modulated by PNS, which may be a crucial factor. We hypothesize that PNS modulates the abnormal integration of sensory and motor information to relieve dystonia ( Figure 2B ), similar to traditional alleviating maneuvers (sensory trick maneuvers) ( 15 , 16 ). Unfortunately, the patient's dystonia started gradually recurring 6 months after surgery despite adequate pain relief, which may have been influenced by persistent abnormal CNS plasticity.…”
Section: Discussionmentioning
confidence: 78%
“…1 Treatment with botulinum toxin requires regular, often painful, injections every 3-4 months, and patients may develop tachyphylaxis over time. Other nonsurgical management options include ocular surface lubrication, increasing tear availability with punctal plugs/cautery, systemic medications such as trihexyphenidyl and sedatives, and sensory trick utilization 5 such as pressure pads mounted on glasses, 6 glare and wind trigger reduction through tinted glasses or wrap around glasses, and ptosis props. These management options reduce rather than eliminate symptoms, are often used JMD in combination, and have variable benefits for patients.…”
Section: Jmdmentioning
confidence: 99%